Molecular insight into thymoquinone mechanism of action against Mycobacterium tuberculosis - Jankowski, Grzegorz; Sawicki, Rafał; Truszkiewicz, Wiesław; Wolan, Natalia; Ziomek, Marcin; Hryć, Benita; Sieniawska, Elwira (Frontiers in Microbiology, 2024)
Natural products are promising antimicrobials usually having multiple and different cellular targets than synthetic antibiotics. Their influence on bacteria at various metabolic and functional levels contributes to higher efficacy even against drug-resistant strains. One of such compounds is a naturally occurring p-benzoquinonethymoquinone. A plant-derived natural product, thymoquinone,It is effective against different bacteria, including multidrug-resistant, and extremely drug-resistant Mycobacterium tuberculosis. Its antibacterial mechanism of action was studied in several bacterial species however other than mycobacteria. To get an insight into antimycobacterial activity of thymoquinone at the molecular level Wwe performed metabolomic and transcriptomic analyses to understand its molecular mechanism of action in this speciesof bacteria exposed to this compound.. The expression of genes coding stressresponsive sigma factors revealed that thymoquinone rapidly induces production of sigE transcripts. At the same time, prolonged influence results in overexpression of all sigma factors genes and significantly upregulates sigF. The metabolomic analysis confirmed that the antimycobacterial activity of thymoquinone was related to the depletion of NAD and ATP pools and downregulation of plasma membrane lipids. This state was observed after 24 h and was persistent the next day, suggesting that bacteria could not activate catabolic mechanisms and produce energy. Additionally, the presence of thymoquinone nitrogen derivative in bacterial broth and the culture was reported.